A re-examination of ENSO/ anti-ENSO events and simultaneous performance of the Indian summer monsoon - CHATTOPADHYAY, J.; BHATLA, R. (MAUSAM, 1996)
The relationship between ENSO/anti-ENSO events in the Pacific basin and simultaneous all India monsoon has been re-examined for the period 1901-1990 using Southern Oscillation Index (SOI). The result shows that there is fairly strong association between ENSO events and dry monsoon years. There exists a weak teleconnection between anti-ENSO events and wet monsoon indicating that anti-ENSO events have only a moderate impact on the Indian monsoon rainfall. Developing ENSO (anti-ENSO) episodes during the monsoon season indicates non-occurrence of simultaneous floods (droughts) with a very high degree of confidence 70 (50) percent of the droughts (floods) during the above period have occurred during ENSO (anti-ENSO) events indicating that extreme monsoon activities in the form of droughts (floods) might be important factors for the occurrence of simultaneous ENSO/anti-ENSO events.